EFFECTS OF PH AND SALINITY ON THE INTENSITY OF MAGNETIZATION IN REDEPOSITED SEDIMENTS - Katari K.; Tauxe L. (My University, 2000)
The intensity of magnetization in redeposited sediments was measured as a function of salinity and pH of the sediment-water mixture. The intensity was relatively low at high salinity or low pH. Under these conditions, inter-particle bonds are enhanced, which lead to the formation of larger flocs. Ferromagnetic minerals (magnetite in our sediment) are incorporated in the flocs consisting mainly of non-magnetic minerals, and orientation along an applied field is resisted by the drag proportional to the third power of the diameter of the floc. Higher intensity is recorded at lower salinity and higher pH, when inter-particle forces are weaker, and floc sizes are smaller. The increase of magnetization as a function of pH stops at a pH of about 5, which is the PZC of the edge of illite (the dominant non-magnetic mineral in our sediment). Above this pH, both the edge and face of the illite grains are negative, and there is net repulsion, which retards flocculation. The interactions between clay particles therefore have a larger effect on the intensity of magnetization than interactions between magnetite and clay. This suggests that magnetite is always included in a clay-magnetite domain, and this domain is the smallest unit that is reoriented by a magnetic field.
Keywords: FLOCCULATION; MAGNETIC INTENSITY; PALEOMAGNETISM; SEDIMENTS; SURFACE PROPERTIES